Development of a Modern Citizen Core Literacy Test for Middle School Students - Yen-Chun Chen; Su-Pin Hung (National Taipei University of Education, 2019)
The purpose of this study was to design the Modern Citizen Core Literacy Test with well reliability and validity for middle school students. To develop the test, the core competency index as well as the assessment framework of the International Civic and Citizenship Education Survey were used as references. The Modern Citizen Core Literacy Test is developed to reflect the life experiences of middle school students. To establish content validity of the test, a panel of experts from middle schools were invited to review the first version of the test. After a pilot study, the test was administered to a total of 1,479 students from 22 middle schools in Taiwan; they were recruited with stratified purposive sampling. Multi-dimensional Partial Credit Model was used to assess the model-data fit. Five-core literacy were identified: moral literacy, democracy literacy, scientific literacy, media literacy and aesthetic literacy. Moreover, the test showed sufficient internal consistency with person separation reliability ranging from .593 to .882. The Split-half reliability is .883. In addition, the present study adopted item response theory based validation procedure. The results revealed that five dimensions of the Modern Citizen Core Literacy Test exhibited an acceptable model-data fit. Criterion-related validity, interpretability evidence, generalizability evidence, and substantive evidence were all supported, indicating that the test has good reliability and validity.